Analisis Keandalan Bangunan Irigasi pada Daerah Irigasi (DI) Jangkung, Kabupaten Malang - Arie Fahrurozi; Danang Bimo Irianto; Pamela Dinar Rahma (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
The Jangkung Irrigation District (DI) in Dadapan Village, Wajak Subdistrict, Malang Regency, is a vital piece of infrastructure serving 39 ha of farmland. As it ages, this irrigation system is experiencing a decline in performance due to the physical degradation of its infrastructure. This study aims to evaluate the physical performance of the Jangkung DI infrastructure to determine the health status of the network and prioritize its maintenance. The methodology employed combines qualitative visual inspections in the field with quantitative analysis based on Ministry of Public Works and Public Housing Regulation No. 12/PRT/M/2015. The assessment focused on five main components of the physical infrastructure: main structures, conveyance channels, structures along the conveyance channels, drainage channels, and inspection roads. The results of the study show that the Main Structures have a performance weight of 78.00%, indicating that structural integrity remains good but is hindered by invasive vegetation. Meanwhile, the Conveyance Channels recorded a score of 58.04%, Structures on Conveyance Channels 52.50%, Discharge Channels 50.00%, and Inspection Roads 55.00%. Cumulatively, the Irrigation System Performance Index (IKSI) for the Jangkung Irrigation District (DI Jangkung) is 59.79%. According to standard classifications, this rating places the Jangkung Irrigation System in the “Damaged” category, where the system’s functionality is severely impaired and requires major repairs or replacement. Recommended technical measures include normalizing the drainage channels, routinely clearing vegetation, and making permanent repairs to the water gates to maintain the efficiency of water distribution to farmers.